An Introduction and Review of the Manuscript of the Pandit Lachhmi Ram Sarwar Lakhnavi’s Dewan - Afzal, Amna; Farid, Sayyid Muhammad (sourcecoder, 2024)
Persian language and literature have a rich and deep-rooted history in the Indian subcontinent. The arrival of Iranian poets in India created a fertile environment for local poets to adopt Persian as a medium for their poetic expressions. This attraction to Persian was not limited to Muslim poets; people of other faiths, particularly Hindus, also embraced the language. Among these poets was Pandit Lachhmi Ram Sarwar Lakhnavi, a prominent Persian poet from the subcontinent during the latter half of the 12th century Hijri and the early half of the 13th century Hijri. He initially resided in Kashmir before migrating to Lucknow. His dewan, or collection of poetry, comprises three hundred ghazals, two tarji’-bands, and one masnavi. There are three known manuscripts of his dewan: two are preserved in the library of Punjab University in Lahore, Pakistan, and one is housed in the British Museum in London, United Kingdom. This article examines these versions in detail.